Quantifier Scope in German. - Pafel, Jürgen (John Benjamins Pub. Co., 2006)
This book presents a comprehensive account of quantifier scope in German. The author investigates scope behavior of ordinary quantifiers and negative, adverbial, interrogative, relative and particle quantifiers. The areas which are dealt with include: relative scope in simple sentences, absolute and relative scope in complex sentences, noun-phrase internal scope, and scope behavior of indefinite noun phrases. A theory of explicit and implicit quantification is proposed and a uniform process of scope determination is sketched which encompasses the scope of explicit as well as implicit quantifie.